2021
DOI: 10.1186/s13073-021-00986-9
|View full text |Cite
|
Sign up to set email alerts
|

A small number of early introductions seeded widespread transmission of SARS-CoV-2 in Québec, Canada

Abstract: Background Québec was the Canadian province most impacted by COVID-19, with 401,462 cases as of September 24th, 2021, and 11,347 deaths due mostly to a very severe first pandemic wave. In April 2020, we assembled the Coronavirus Sequencing in Québec (CoVSeQ) consortium to sequence SARS-CoV-2 genomes in Québec to track viral introduction events and transmission within the province. Methods Using genomic epidemiology, we investigated the arrival of S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 57 publications
(48 reference statements)
4
16
0
Order By: Relevance
“…The phylogenetic diversity of SARS-CoV-2 genomes we report in this local outbreak is consistent with the genomic diversity observed across Quebec at the time, specifically subclades B and B.1 [ 33 ]. However, we found that different lineage assignment methods we employed (Pangolin, NextClade, phylogeny, dominant haplogroups and PHATE dimensionality reduction) produced disparate results.…”
Section: Discussionsupporting
confidence: 84%
“…The phylogenetic diversity of SARS-CoV-2 genomes we report in this local outbreak is consistent with the genomic diversity observed across Quebec at the time, specifically subclades B and B.1 [ 33 ]. However, we found that different lineage assignment methods we employed (Pangolin, NextClade, phylogeny, dominant haplogroups and PHATE dimensionality reduction) produced disparate results.…”
Section: Discussionsupporting
confidence: 84%
“…For each candidate species, the animal-derived sequences, and their closest relative human-derived sequence were combined with ten random sub-samplings of human-derived sequences (n ≈ 50 per subtree per month of the pandemic), from which we inferred ten replicate phylogenies per species, providing an assessment of phylogenetic uncertainty. Using ancestral state reconstruction as previously described (Murall et al 2021), we counted the most basal animal-to-human ( Figure 1a-d ) and human-to-animal transitions on each tree ( Supplementary Table S2 ). To determine a lower bound for the transmission counts, we excluded transition branches with <75% bootstrap support (Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, correlating Tajima's D values with epidemiological data at finer geographical scale might improve its explanatory power and inform public health agencies about the epidemiological trends. Essentially, Tajima's D can be used in combination with effective reproductive numbers (R) to estimate the spread of an expanding population in a given region ( 13 ). More recently a Genomic Identity (GENI) score (a genome diversity metric) was formulated from SARS-CoV-2 genomic data to estimate outbreak trends that lead to the emergence of new variants ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, effective reproductive number (R) is a widely used metric to define outbreaks and to measure COVID19 disease spread ( 11 ). Tajima's D ( 12 ), a classical population genetics approach, can also be used to investigate SARS-CoV-2 lineage expansions ( 13 ). Dimensionality reduction techniques summarizing genetic diversity are also widely employed to investigate population structure in various species, and in particular, principal component analysis (PCA) has been proposed to investigate the population structure of SARS-CoV-2 virus early in the pandemic ( 14 ).…”
Section: Introductionmentioning
confidence: 99%